DESIGN, SIMULATION AND ANALYSIS OF AN INTELLIGENT LEAD-ACID BATTERY CHARGER FED BY SOLAR SYSTEM - S. Maraud, Hussain; M. Abdulbaqi, Isam; I. Majeed, Ammar (Journal of Engineering and Sustainable Development, 2016)
The objectives of this work are to design, simulate and analyze the operation of an intelligent lead-acid battery charger supplied from two (250W) nominal power, Photovoltaic (PV) panels in parallel to charge two (200Ah) capacity lead-acid batteries in parallel. The storage battery’s effectiveness depends on the charging process. Hence, this research deals with the study, simulation, and design of an intelligent charger fed by the solar system due to the latest technologies. The developed charging method entitled "the decreased charging current based on SOC" is adopted in this research to charge a lead-acid battery. The principle of decreased charging current is to make the real charging current as close as possible to the maximum acceptable current. The advantage of this technique is to mix the rapidity of charging and prevents overcharging and generating gases. Also, the design considers different operating conditions of load, battery state of charge (SOC), and ambient effect in order to achieve the best charging condition of the batteries and to be compatible with the user requirements. Therefore, this technique of charging can be considered intelligent charging compared to traditional charging ways, which are often either a constant charging current or a constant charging voltage. The flexible, simple, and cheap design is the objective of this research. The obtained results agree with the research objective.